Reference Identification in Translation and Interpretation - Svane, Brynja (HERMES - Journal of Language and Communication in Business, 2017)
Reference identification is fundamental in any kind of human communication and decisive for the understanding of what others are trying to communicate. But it is not evident that speakers and hearers attach the same value to specific references to the real world that they exchange in an interaction. After a brief introduction to the problem different aspects of the relationship between specific and non-specific references in translation and interpretation are discussed and an analysis of potential strategies toward the translation of references is undertaken.